Biological Nurturing and Baby-Led Feeding Techniques for Pain Reduction in Post-Caesarean Mothers - Limbong, Magdalena; Riawahyuni, Riawahyuni; Kasim, Erna; Nurbaiti, Nurbaiti (Inspirasi Foundation, 2025)
Introduction: Postoperative sectio caesarea pain management can be done by pharmacological and non-pharmacological means, among others by applying complementary therapy biologic nurturing baby led feeding is one of the non-pharmacological therapies by distraction or diversion. One example of distraction is by adjusting the position of breastfeeding. Research objectives: this case study aims to determine the effect of the implementation of biologic nurturing baby led feeding techniques in reducing the pain scale in post sectio caesarea mothers. Method: case study method using descriptive method with 2 respondents and conducted for 3 days in the Baji Gau room of Labuang baji Hospital Makassar. Research instruments used observation scale sheet, SOP, medical record data, and breast milk production observation. Methods of data collection by interview and observation. Data analysis and data presentation were carried out in textual or narrative form and tables. Results: the implementation of the implementation in both respondents decreased after each implementation by 1 level. Conclusion: it can be concluded that the implementation of biologic nurturing baby leed feeding techniques can reduce pain in post sectio caesarea mothers. Suggestion: it is recommended that the author further improve in applying the existing theory in real terms, especially related to the implementation of biologic nurturing baby leed feeding techniques in reducing the pain scale in post sectio caesarea mothers for the next level of education.